Efecto relajante del extracto alcohólico de las hojas de Eupatorium gayanum wedd (Asmachilca), sobre organos aislados de rata - Bonilla R., Pablo (2006)
In the present investigation was determined the chemicals groups predominant in the extract etanolic of leafes of Eupatoriun gayanum Wedd (asmachilca), it was compounds fenolics and flavonoids in more cuantity. lt proved the relaxing effect of the extract etanolic of leafes of Eupatorium gayanum on aislated organs by means of Hazekamp's et al. method to (200l). The extract etanolic of leafes of asmachilca has been demonstrated the relaxing effect of easing on the smooth muscle endotraqueal, that help to explique the anti-asthmatic effect and that should to the high place contained in flavonoids, equally has been observed relaxing activity on the aorta, duodenum and ileon of rates.